2014
DOI: 10.1007/s12070-014-0788-1
|View full text |Cite
|
Sign up to set email alerts
|

Sialolipoma of Minor Salivary Glands: Presentation of Five Cases and Review of the Literature with an Epidemiological Analyze

Abstract: Sialolipoma is rare benign neoplasm arise from salivary glands (majors and minors) characterized by neoplastic adipose tissue with scattered non-neoplastic salivary gland acinus. To date 60 cases (including 5 cases reported in the present paper) have been reported in scientific literature. This article presents 5 new cases of sialolipoma affecting minor salivary glands (MiSG) and additionally reviews and analyzes the previously published cases to assess possible demographical differences between sialolipoma fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
1
10
1
Order By: Relevance
“…Our results, in conjunction with previous reports, show that sialolipomas occur at any age, ranging from newborns to the elderly (mean age 47.1 years). Although previous studies have reported male predominance, 1,12,23 the review of published cases, including the current series, revealed a female preponderance (58.2%), with a female‐to‐male ratio of 1.3:1. Also, differences were observed in the age distribution between sialolipomas of the minor and major salivary glands (Table 1).…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Our results, in conjunction with previous reports, show that sialolipomas occur at any age, ranging from newborns to the elderly (mean age 47.1 years). Although previous studies have reported male predominance, 1,12,23 the review of published cases, including the current series, revealed a female preponderance (58.2%), with a female‐to‐male ratio of 1.3:1. Also, differences were observed in the age distribution between sialolipomas of the minor and major salivary glands (Table 1).…”
Section: Discussioncontrasting
confidence: 61%
“…The term sialolipoma was first introduced in 2001 by Nagao et al, to describe tumours characterised by well‐delimitated proliferation of mature adipose tissue with secondary involvement of the salivary gland parenchyma 1 . Since then, 75 well‐documented cases of sialolipomas reported in the literature and 10 new cases in the current series are described involving major and minor salivary glands, 1,3‐28 highlighting the rarity of this lesion. To the best of our knowledge, this study is the first multi‐institutional retrospective study with the largest sample of sialolipomas.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The size of hard palate sialolipomas (1–1.8 cm) and their age distribution reported in the literature are closer to that of the present case. [ 1 2 3 4 5 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] To our knowledge, less than 10 cases from the hard palate are reported. [ 1 2 3 4 5 6 ] Here, we report a case of hard palate sialolipoma, peculiar by the intratumor malformation-type vascular patterns.…”
Section: Introductionmentioning
confidence: 99%